Problems of auditing using quality management systems for sustainable development of organizations - Kaziliūnas, Adolfas (Technological and Economic Development of Economy, 2008)
The role of international standards is analysed in accordance with the quality management of organisations by the requirements of sustainable development. Organisations and companies become increasingly dependent on each other and foreign partners in business, prosperity, socio‐economic change and environment responsibility. There is an essential necessity for using International Standards under these changing conditions. The management systems standards ISO 9001 (quality) and ISO 14001 (environment) have gained recognition in Lithuania. ISO 9001:2000 is approaching 750 and ISO 14001 is approaching 140 certifications across a diverse range of organisations in the manufacturing, service and government areas. The narrow view of quality management has now been swept aside by ISO 9000:2000 quality management principles that aim to help organisations achieve sustained success. But there are some difficulties in implementing these principles. Auditors are responsible for correct implementation of standards. For the auditors they represent a key for transforming the way quality system audits, as recognised by the International Accreditation Forum (IAF). Too many auditors lack real interpersonal skills or experience to engage effectively both main board directors and the shop floor workers. It is very important that auditors must have sufficient preparation, training and gravitas and will be reluctant to engage top management and have capability to interface at this level. The main topics of how to manage quality audit according to the requirements and new quality management principles of ISO 9000:2000 standards are presented in this article. It also provides recommendations on the management of audit programmes, the conduct of internal or external audits of quality management systems, as well as on the competence and evaluation of auditors. This article provides auditors with effective questioning techniques that will enable them to establish that an organisation is managing its processes effectively.Kokybės vadybos sistemų audito problemos siekiant darnaus organizacijų vystymosiSantrauka. Straipsnyje analizuojamas tarptautinius standartus atitinkančių kokybės vadybos sistemų vaidmuo darniam organizacijų vystymui. Įmonės ir organizacijos vis daugiau tampa priklausomos viena nuo kitos ir užsienio partnerių verslo, socialinėse, ekonominėse bei aplinkosaugos srityse. Šiomis sąlygomis labai naudinga pasinaudoti tarptautiniais standartais, nes jie padeda vienodai suprasti ir suderinti daugelį kriterijų. Lietuvoje pastaraisiais metais didžiausio populiarumo sulaukė tarptautiniai standartai ISO 9000:2000 (kokybė) ir ISO 14000 (aplinkosauga). Lietuvos gamybiniame, paslaugų ir viešajame sektoriuose jau yra apie 750 organizacijų, įdiegusių kokybės vadybos sistemas pagal ISO 9001:2000 standartą, ir apie 140 organizacijų, įdiegusių aplinkos vadybos sistemas pagal ISO 14001 standartą. ISO 9000:2000 standartai reikalauja esminių organizacijos požiūrių į vadybą pokyčių. Vadybos sistemos turi padėti kurti pridedamąją organizacijos vertę. Standartuose išreikštas požiūris, kad organizacijos tikslai turi būti pasiekiami efektyviai ir rezultatyviai valdant procesus ir jų sąveiką, iš esmės keičia auditų atlikimo būdą, nes auditoriai yra atsakingi už teisingą standartų nuostatų traktavimą ir įgyvendinimą. Auditoriai turi išmokti naujos audito atlikimo technikos, kuri leistų auditoriams nustatyti, ar organizacija efektyviai valdo procesus ir pasiekia užsibrėžtų tikslų. Tai nėra lengvas uždavinys ir susiduriama su nemažais sunkumais. Straipsnyje nagrinėjamas šių sunkumų pobūdis ir pateikiami kai kurie jų įveikimo būdai, analizuojama audito metodologija, tinkamo klausimyno sudarymas bei audito atlikimo technika, kaip to reikalauja ISO 9000:2000 standartų kokybės vadybos principai.Reikšminiai žodžiai: vadybos sistemos, ISO standartai, kokybės / aplinkos sistemų auditas.First published online: 21 Oct 2010